Mastering SciPy - Francisco Javier Blanco-Silva; Francisco Javier B Silva (Packt Publishing, 2015)
Dive into 'Mastering SciPy' to unlock the full potential of the SciPy ecosystem for scientific computation and data analysis. This book thoughtfully combines mathematical concepts with Python programming to tackle real-world computational challenges.What this Book will help me doEffectively implement algorithms for data interpolation, approximation, and function optimization.Develop strategies for managing large datasets and performing linear algebra computations.Create and solve differential equations for scientific modeling and simulations.Apply advanced data analysis, statistical methods, and machine learning algorithms.Utilize computational geometry techniques for applications in engineering and data science.Author(s)The authors, None Blanco-Silva and Francisco Javier B Silva, are practitioners and educators in scientific computing and Python programming. They bring a wealth of experience in using SciPy to solve practical scientific challenges. Their clear and engaging approach makes these complex topics accessible and applicable.Who is it for?This book is tailored for professionals and researchers who use Python and are familiar with numerical methods. If you are looking to deepen your understanding of SciPy's capabilities to solve scientific and engineering problems, this book is ideal for you. Readers with a background in IPython and computational mathematics will benefit the most. Beginners in scientific Python can also learn by following the hands-on examples and clear explanations.